Pengaruh Penambahan Tepung Daun Kelor (Moringa oleifera) Pada Pakan Buatan Terhadap Pertumbuhan Dan Tingkat Kecerahan Warna Benih Ikan Komet (Carassius auratus) - Juliana; Mardian Nusi; Mulis (Transbahasa, 2024)
The demand for ornamental fish is increasing every year, one of the most popular ornamental fish is comet fish. Feed is a very important factor in supporting the quality of comet fish produced. In terms of improving the color quality of comet fish, the feed given must contain karatonoid as a color-forming content of comet fish. Moringa leaves are one of the ingredients that contain karatoneids and are an alternative pigmentation factor for ornamental fish. Feeding dosage is also a factor that needs to be considered in the maintenance of comet fish. Feed raw materials that have been formulated are first weighed one by one to match the feed formulation that has been determined. This study was conducted for 42 days by measuring the growth and brightness of fish color once a week. Feeding was carried out 3 times a day, namely in the morning, afternoon, and evening with a dose of feeding in each treatment of 10%, 15%, 20%, and 25%. This study used a complete randomized design. The results showed that the average change in fish body length during the observation of each treatment experienced an increase during maintenance, where the highest treatment was in treatment D by 1.69 cm. Observation of absolute weight is a parameter observed to determine the effect of feed containing moringa flour on comet fish. The highest average absolute weight growth rate at the end of the study was in treatment D amounting to 2.63 gr.